The use of WhatsApp in learning English during pandemic Covid-19: Students’ perception - Zul Astri; Kasmawati; Fhadli Noer; Wahab, Isnaeni (Journal for Teaching and Education for Scholars, 2022)
There is no denying that digital technology permeates every aspect of modern life. One of the technology products is WhatsApp. During the pandemic covid-19, teaching and learning using WhatsApp in Indonesia is carried out for various fields of study, one of which is in teaching and learning English. The objectives of this study are to find out the students’ perceptions of learning English through WhatsApp and describe the media that they need in learning English. The research method to be used is a method based on a descriptive method concerning quantitative approach. The research instrument in data collection was a questionnaire. The study shows that the use of WhatsApp as a learning medium during the Pandemic did not help students in learning English because WhatsApp did not provide qualified features for holding large numbers of Call meetings. Furthermore, media that can be used in call meetings are zoom and google meet because both can accommodate large numbers in one call.